Falling short : the bildungsroman and the crisis of self-fashioning - Stević, Aleksandar (University of Virginia Press, 2020)
"This book examines the defining role of failure and inaction in the history of the bildungsroman in nineteenth- to early twentieth-century Europe"-- Provided by publisher.
Keywords: Bildungsromans -- History and criticism.; European literature -- History and criticism.; Failure (Psychology) in literature.; Maturation (Psychology) in literature.; Self-realization in literature.; Littérature européenne -- Histoire et critique.; Échec dans la littérature.; Maturation (Psychologie) dans la littérature.; Réalisation de soi dans la littérature.; LITERARY CRITICISM / Semiotics & Theory; Bildungsromans; European literature; Failure (Psychology) in literature; Maturation (Psychology) in literature; Self-realization in literature; Criticism, interpretation, etc.